(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article emphasizes the important role of spiritual values and cultural heritage in the spiritual well-being of society. Based on the values, heritage and traditions left by ancestors, each nation grows and develops. People who are indifferent to the spiritual and cultural heritage of their own people live in poverty. In such an atmosphere, indifference, anxiety, pessimistic sentiments intensify, the struggle against oppressors is weakened, conflicts and disagreements within the nation grow.